Barotrauma Telinga Tengah (Middle Ear Barotrauma) - Sumandari, Astri (Jurnal Syntax Fusion, 2022)
The human ear consists of 3 main parts, there are the outer ear, middle ear and inner ear. One of the injuries that can affect the human ear is barotrauma. Barotrauma is an injury caused by a pressure difference between the inside of the body and the external space. Barotrauma can occur in any structure in the body where there is an enclosed space that can be occupied by air including the middle ear space, paranasal sinuses, lungs, stomach and intestines. However, barotrauma most commonly occurs in the middle ear, this is mainly due to the complexity of the function of the eustachian tube. Middle ear barotrauma occurs when the eustachian tube cannot open to balance air pressure. In various literatures it is reported that the incidence and prevalence of ear barotrauma ranges from 4.1 – 82%. Clinical manifestations of middle ear barotrauma include hearing loss, pain in the ear, autophony, a feeling of water in the ear and sometimes accompanied by tinnitus and vertigo.